Biomass-derived dendritic-like porous carbon aerogels for supercapacitors. (20th August 2016) - Ma, Yu-zhu; Guo, Yan; Zhou, Cong; Wang, Cheng-yang
Abstract: Three-dimensional (3D) dendritic-like hierarchical porous carbon areogels (PCAs) have been fabricated via a simple and efficient solvent exchange method followed by an activation process. The natural and renewable biomass material, leonardite fulvic acid (LFA) is used as the carbon source. The hierarchical porous structures are composed of numerous nanospheres with interconnected 3D carbon architectures which are in favor of enhancing the electrical conductivity and facilitating ion transport by providing small resistances and short diffusion pathways. The resultant PCAs are advantageous as electrodes for electrochemical energy storage. For example, the PCAs2 sample exhibits a superior high specific capacitance of 368 F g −1 at a current density of 0.05 A g −1 in 6 M KOH electrolyte, which can still remain 228 F g −1 when the current density increases to 100 A g −1 . The sample also has outstanding cycling stability with capacitance retention of 98.4% after 10, 000 cycles. Remarkably, it is shown that the PCAs2 sample exhibits outstanding electrochemical performance in an organic electrolyte as well. It has an energy density of 43.50 Wh kg −1 at a power density of 33.85 W kg −1 and still maintains 23.25 Wh kg −1 at a power density of 5.89 kW kg −1 . This suggests that the 3D hierarchical PCAs should be a competitive and promising supercapacitor electrode material.